Social Thoughts of Saint Dadu Dayal: A Re-evaluation in Contemporary Context: संत दादूदयाल के सामाजिक विचार: समकालीन संदर्भ में पुनर्मूल्यांकन - Chamoli, Amit; Bairwa, Vinod Kumar (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Saint Dadu Dayal is regarded among the great saints of medieval India who raised a strong voice against social evils, casteism, religious pretensions, and inequalities prevalent in society. He was born at a time when Indian society was afflicted with various social and religious ills. Dadu Dayal adopted the path of Nirguna Bhakti (worship of the formless divine) and through his teachings spread the message of humanity, equality, love, and truth. He believed that God does not reside within the boundaries of any single religion, caste, or place, but is present in every living being. Rejecting caste-based discrimination, Saint Dadu clearly proclaimed that all humans are children of God and share the same soul. By breaking down the barriers of temples and mosques, he placed humanity above religion. His social thought emphasized women’s equality, the dignity of labor, religious tolerance, and moral values of life. This research paper seeks to present a comprehensive evaluation of the social ideas of Saint Dadu Dayal, analyzing how revolutionary his thoughts were in his time and how relevant they remain in today’s social context. Abstract in Hindi Language: संत दादूदयाल मध्यकालीन भारत के उन महान संतों में गिने जाते हैं, जिन्होंने समाज में फैली हुई कुरीतियों, जातिवाद, धार्मिक आडंबर और सामाजिक विषमता के विरुद्ध सशक्त स्वर उठाया। उनका जन्म ऐसे समय में हुआ जब भारतीय समाज अनेक प्रकार की सामाजिक और धार्मिक बुराइयों से ग्रस्त था। दादूदयाल ने निर्गुण भक्ति मार्ग को अपनाया और अपने उपदेशों के माध्यम से मानवता, समानता, प्रेम और सत्य का प्रचार किया। उनका मानना था कि ईश्वर का निवास किसी एक धर्म, जाति या स्थान तक सीमित नहीं है, बल्कि वह हर जीव में विद्यमान है। संत दादू ने समाज में प्रचलित जातिगत भेदभाव को नकारते हुए स्पष्ट रूप से कहा कि सभी मनुष्य ईश्वर की संतान हैं और सभी में एक ही आत्मा का निवास है। उन्होंने मंदिर-मस्जिद की दीवारों को तोड़कर मनुष्यता को धर्म से ऊपर रखा। उनके सामाजिक विचारों में नारी की समानता, श्रम की प्रतिष्ठा, धार्मिक सहिष्णुता और नैतिक जीवन मूल्यों पर विशेष बल दिया गया है। यह शोध पत्र संत दादूदयाल के सामाजिक विचारों का समग्र मूल्यांकन करने का प्रयास है, जिसमें यह विश्लेषण किया गया है कि उनके विचार उस समय के समाज में कितने क्रांतिकारी थे और आज के सामाजिक परिप्रेक्ष्य में उनकी कितनी प्रासंगिकता है। Keywords: संत दादूदयाल, सामाजिक विचार, निर्गुण भक्ति, समानता, जातिवाद, धार्मिक दादूपंथ।